2019
DOI: 10.3389/fimmu.2019.00893
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Myeloid-Derived Cells in the Progression of Liver Disease

Abstract: Control of homeostasis and rapid response to tissue damage in the liver is orchestrated by crosstalk between resident and infiltrating inflammatory cells. A crucial role for myeloid cells during hepatic injury and repair has emerged where resident Kupffer cells, circulating monocytes, macrophages, dendritic cells and neutrophils control local tissue inflammation and regenerative function to maintain tissue architecture. Studies in humans and rodents have revealed a heterogeneous population of myeloid cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 257 publications
(284 reference statements)
4
83
2
Order By: Relevance
“…Identification of an apparently protective CD68+CD14+ cell population (Fig. ) is similar to other studies of tolerogenic livers and a recent study of human intrahepatic macrophages that analyzed populations using single‐cell RNA sequencing, where they had immunoregulatory and patrolling type functions . Three main macrophage clusters were significantly increased in patients who were HCV‐positive with advanced fibrosis when compared to controls, and included CD163+CD16+, CD68+, and CD68+MAC387+.…”
Section: Discussionsupporting
confidence: 81%
“…Identification of an apparently protective CD68+CD14+ cell population (Fig. ) is similar to other studies of tolerogenic livers and a recent study of human intrahepatic macrophages that analyzed populations using single‐cell RNA sequencing, where they had immunoregulatory and patrolling type functions . Three main macrophage clusters were significantly increased in patients who were HCV‐positive with advanced fibrosis when compared to controls, and included CD163+CD16+, CD68+, and CD68+MAC387+.…”
Section: Discussionsupporting
confidence: 81%
“…The identification of a CD68+CD14+ cell population thought to have pro-inflammatory, immunoregulatory, and patrolling type functions, similar to previous findings in tolerogenic livers, and a recent study of human intrahepatic macrophages that analyzed these populations with single-cell RNA sequencing (7,15). This study also confirmed the accumulation of different macrophage populations (Suppl Fig 4) that were previously shown to be increased in patients with chronic HCV or in human monocytes cultured with HCV-infected hepatocytes (5,12,13,32,37).…”
Section: Discussionsupporting
confidence: 87%
“…HCV induces activation of signaling pathways that promote alternative macrophage activation (M2) and results in increased expression of pro-(M1) and anti-inflammatory (M2) cytokines (12,13), which enhances overall hepatic inflammation and development of fibrosis by promoting differentiation of hepatic stellate cells (11,13). However, it is now widely accepted that the "M1" and "M2" classification for macrophages is an over simplification since they exhibit extensive plasticity and change between homeostatic and pathologic conditions (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…This was further confirmed by the high expression of transcripts enriched in Kupffer cells: Clec4f, Timd4 (Tim4), CD68, CD163, Siglec1 (CD169), Marco, Fcgr1 and Fcgr4 . The expression of genes characteristic of recruited monocyte‐derived macrophages [Itgam (CD11b), Cxcl10] and monocyte adhesion and migration‐promoting proteins (Lama4, Itga6) was considerably lower compared to the β‐gal − F4/80 high macrophages. Interestingly, the β‐gal + F4/80 high cells were characterized by high expression of microglial markers TREM2 and Aif‐1 (Iba‐1) , TYROBP (DAP12), the key signalling adaptor associated with TREM2 and TREM2‐shedding metalloproteinases ADAM10 and ADAM17.…”
Section: Resultsmentioning
confidence: 74%